2010
DOI: 10.1016/j.febslet.2010.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human immunodeficiency virus gp120 with the voltage‐gated potassium channel BEC1

Abstract: a b s t r a c tRetrovirus replication critically depends on a dynamic interplay between retroviral and host proteins. We report on the binding of the surface subunit (glycoprotein 120 (gp120)) of the human immunodeficiency virus type 1 (HIV-1) envelope protein (Env) to the cytoplasmic C-terminus of the voltage-gated potassium channel BEC1 (brain-specific ether-a-go-go-like channel 1), an interaction that can result in the repression of BEC's activity and the inhibition of HIV-1 particle-release. BEC1 protein w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Further studies using inside-out patch clamping confirmed Nef-mediated inhibition of large-conductance Ca 2+ -dependent K + channels (BK Ca ) [21,22], but the effects of BK Ca modulation during the HIV-1 life cycle were not investigated [16]. HIV-1 gp120 and viral protein U (Vpu) have also been shown to affect K + channel activity, which is 2+ release via two-pore Ca 2+ channels (TPC) 1 and 2.…”
Section: Ion Channels and Virus Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…Further studies using inside-out patch clamping confirmed Nef-mediated inhibition of large-conductance Ca 2+ -dependent K + channels (BK Ca ) [21,22], but the effects of BK Ca modulation during the HIV-1 life cycle were not investigated [16]. HIV-1 gp120 and viral protein U (Vpu) have also been shown to affect K + channel activity, which is 2+ release via two-pore Ca 2+ channels (TPC) 1 and 2.…”
Section: Ion Channels and Virus Persistencementioning
confidence: 99%
“…Gp120 binding to the cytoplasmic C terminus of the ether-a-go-go (hERG) K + channel (also known as K v 11.1) and its subsequent inhibition enhanced virus particle release, which could be blocked by hERG channel overexpression [21]. HIV-1 Vpu was also reported to manipulate the resting membrane potential through interference with background leak K + channels [23,24].…”
Section: Ion Channels and Virus Persistencementioning
confidence: 99%
“…For example, the Hepatitis C virus non-structural protein NS5A modulates the function of Kv2.1, a voltage-gated K + channel 27 and regulates cell apoptosis. HIV-1 protein Nef alters the intracellular K + ion concentration 30 by targeting large-conductance Ca 2+ -dependent K + channels (BK Ca ) 31 whereas viral Env protein, gp120 inhibits the voltage-gated K + channel (BEC1) activity resulting in decreased virus release 32 . HIV gp120 induces hippocampal neuronal apoptosis by enhancement of Kv channel functions through p38 MAPK phosphorylation in HIV associated neurocognitive disorder 33 .…”
Section: Introductionmentioning
confidence: 99%
“…G-protein coupled receptors are also associated with ion channel activity [ 374 ]. R5-gp120 can suppress the activity of the voltage gated K + channel BEC1 in 293 T cells [ 377 ] and X4-tropic envelope can increase the phosphorylation of Kv1.3 channels and induce membrane depolarization in T-cell lines [ 378 ]. In human macrophages, X4 and R5 gp120 can elicit Ca 2+ -activated K + currents, Cl − currents, and Ca 2+ -permeant nonselective cation currents, which are blocked by the specific CXCR4 antagonist, AMD3100, or in cells from donors homozygous for the CCR5- 32 mutation, respectively [ 374 , 379 ].…”
Section: Hiv Activation Of Co-receptorsmentioning
confidence: 99%